Use of web pages in environmental education: Preferences of primary education teachers in the selection of content - Zambrana Tévar, Claustro; Torquemada Vidal, Asunción (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Primary Education is the ideal time to instill proactive behaviors in young people around current environmental challenges. Analyzing the benefits of using Environmental Education websites, this research addresses the characteristics that these sites must have to fulfill their didactic function based on the needs shown by a sample of teachers from the Community of Madrid (Spain) from of an ad hoc questionnaire. The results show that the study objectives, motivation and activities proposed to students on websites are the most important aspects in the selection of resources for teachers.